Answer:
A. ![(\sqrt[3]{125})^9\ and\ (125)^{\frac{9}{3}}](https://tex.z-dn.net/?f=%28%5Csqrt%5B3%5D%7B125%7D%29%5E9%5C%20and%5C%20%28125%29%5E%7B%5Cfrac%7B9%7D%7B3%7D%7D)
D. ![8^{\frac{9}{2}}\ and\ (\sqrt{8})^9](https://tex.z-dn.net/?f=8%5E%7B%5Cfrac%7B9%7D%7B2%7D%7D%5C%20and%5C%20%28%5Csqrt%7B8%7D%29%5E9)
Step-by-step explanation:
Equivalent expressions are those expressions that simplify to same form.
Now, let us check each of the given options.
Option A:
![(\sqrt[3]{125})^9\ and\ (125)^{\frac{9}{3}}](https://tex.z-dn.net/?f=%28%5Csqrt%5B3%5D%7B125%7D%29%5E9%5C%20and%5C%20%28125%29%5E%7B%5Cfrac%7B9%7D%7B3%7D%7D)
We know that,
![\sqrt[n]{x} =x^{\frac{1}{n}}](https://tex.z-dn.net/?f=%5Csqrt%5Bn%5D%7Bx%7D%20%3Dx%5E%7B%5Cfrac%7B1%7D%7Bn%7D%7D)
Therefore, ![\sqrt[3]{125} =(125)^{\frac{1}{3}}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B125%7D%20%3D%28125%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D)
Thus the first expression becomes;
![((125)^{\frac{1}{3}})^9](https://tex.z-dn.net/?f=%28%28125%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%29%5E9)
Now, using law of indices
, we get
![((125)^{\frac{1}{3}})^9=((125))^{\frac{1}{3}\times 9}=((125))^{\frac{9}{3}](https://tex.z-dn.net/?f=%28%28125%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%29%5E9%3D%28%28125%29%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%5Ctimes%209%7D%3D%28%28125%29%29%5E%7B%5Cfrac%7B9%7D%7B3%7D)
Therefore,
are equivalent.
Option B:
![12^{\frac{2}{7}}\ and\ (\sqrt{12})^7](https://tex.z-dn.net/?f=12%5E%7B%5Cfrac%7B2%7D%7B7%7D%7D%5C%20and%5C%20%28%5Csqrt%7B12%7D%29%5E7)
Consider the second expression ![(\sqrt{12})^7](https://tex.z-dn.net/?f=%28%5Csqrt%7B12%7D%29%5E7)
We know that,
![\sqrt x=x^{\frac{1}{2}}](https://tex.z-dn.net/?f=%5Csqrt%20x%3Dx%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D)
![(\sqrt{12})^7=((12)^{\frac{1}{2}})^7=(12)^{\frac{1}{2}\times 7}=(12)^{\frac{7}{2}}](https://tex.z-dn.net/?f=%28%5Csqrt%7B12%7D%29%5E7%3D%28%2812%29%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%29%5E7%3D%2812%29%5E%7B%5Cfrac%7B1%7D%7B2%7D%5Ctimes%207%7D%3D%2812%29%5E%7B%5Cfrac%7B7%7D%7B2%7D%7D)
Therefore,
. Hence, the expressions
are not equivalent.
Option C:
![4^{\frac{1}{5}}\ and\ (\sqrt 4)^5](https://tex.z-dn.net/?f=4%5E%7B%5Cfrac%7B1%7D%7B5%7D%7D%5C%20and%5C%20%28%5Csqrt%204%29%5E5)
We know that,
![x^{\frac{1}{n}}=\sqrt[n]{x}](https://tex.z-dn.net/?f=x%5E%7B%5Cfrac%7B1%7D%7Bn%7D%7D%3D%5Csqrt%5Bn%5D%7Bx%7D)
Therefore, ![4^{\frac{1}{5}}=\sqrt[5]{4}](https://tex.z-dn.net/?f=4%5E%7B%5Cfrac%7B1%7D%7B5%7D%7D%3D%5Csqrt%5B5%5D%7B4%7D)
Now, ![\sqrt[5]{4}\ne (\sqrt 4)^5](https://tex.z-dn.net/?f=%5Csqrt%5B5%5D%7B4%7D%5Cne%20%28%5Csqrt%204%29%5E5)
Therefore, the expressions
are not equivalent.
Option D:
![8^{\frac{9}{2} }\ and\ (\sqrt 8)^9](https://tex.z-dn.net/?f=8%5E%7B%5Cfrac%7B9%7D%7B2%7D%20%7D%5C%20and%5C%20%28%5Csqrt%208%29%5E9)
Using law of indices
, we get
![8^{\frac{9}{2} }=(8^{\frac{1}{2}})^9](https://tex.z-dn.net/?f=8%5E%7B%5Cfrac%7B9%7D%7B2%7D%20%7D%3D%288%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%29%5E9)
Now, we know that, ![x^{\frac{1}{2}}=\sqrt x](https://tex.z-dn.net/?f=x%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%3D%5Csqrt%20x)
So, ![(8^{\frac{1}{2}})^9=(\sqrt8)^9](https://tex.z-dn.net/?f=%288%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%29%5E9%3D%28%5Csqrt8%29%5E9)
Therefore,
are equivalent.